Efficacy of the 1-year (13-cycle) segesterone acetate and ethinylestradiol contraceptive vaginal system: results of two multicentre, open-label, single-arm, phase 3 trials. Issue 8 (August 2019) - Archer, David F; Merkatz, Ruth B; Bahamondes, Luis; Westhoff, Carolyn L; Darney, Philip; Apter, Dan; Jensen, Jeffrey T; Brache, Vivian; Nelson, Anita L; Banks, Erika; Bártfai, György; Portman, David J; et al.
Summary: Background: A ring-shaped, contraceptive vaginal system designed to last 1 year (13 cycles) delivers an average of 0·15 mg segesterone acetate and 0·013 mg ethinylestradiol per day. We evaluated the efficacy of this contraceptive vaginal system and return to menses or pregnancy after use. Methods: In two identically designed, multicentre, open-label, single-arm, phase 3 trials (one at 15 US academic and community sites and one at 12 US and international academic and community sites), participants followed a 21-days-in, 7-days-out segesterone acetate and ethinylestradiol contraceptive vaginal system schedule for up to 13 cycles. Participants were healthy, sexually active, non-pregnant, non-sterilised women aged 18–40 years. Women were cautioned that any removals during the 21 days of cyclic use should not exceed 2 h, and used daily paper diaries to record vaginal system use. Consistent with regulatory requirements for contraceptives, we calculated the Pearl Index for women aged 35 years and younger, excluding adjunctive contraception cycles, as the primary efficacy outcome measure. We also did intention-to-treat Kaplan-Meier life table analyses and followed up women who did not use hormonal contraceptives or desired pregnancy after study completion for 6 months for return to menses or pregnancy. The trials are registered withClinicalTrials.gov, numbersNCT00455156 andNCT00263341 . Findings: Between Dec 19, 2006, and Oct 9, 2009, at the 15 US sites, and between Nov 1, 2006, and July 2, 2009, at the 12 US and international sites we enrolled 2278 women. Our overall efficacy analysis included 2265 participants (1130 in the US study and 1135 in the international study) and 1303 (57·5%) participants completed up to 13 cycles. The Pearl Index for the primary efficacy group was 2·98 (95% CI 2·13–4·06) per 100 woman-years, and was well within the range indicative of efficacy for a contraceptive under a woman's control. The Kaplan-Meier analysis revealed the contraceptive vaginal system was 97·5% effective, which provided further evidence of efficacy. Pregnancy occurrence was similar across cycles. All 290 follow-up participants reported return to menses or became pregnant (24 [63%] of 38 women who desired pregnancy) within 6 months. Interpretation: The segesterone acetate and ethinylestradiol contraceptive vaginal system is an effective contraceptive for 13 consecutive cycles of use. This new product adds to the contraceptive method mix and the 1-year duration of use means that women do not need to return to the clinic or pharmacy for refills every few months. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development of the National Institutes of Health, the US Agency for International Development, and the WHO Reproductive Health Research Department.